EFEKTIVITAS STRATEGI PEMBELAJARAN SISWA AKTIF PADA PENINGKATAN PEMAHAMAN KONSEP DAN PENERAPAN PRAKTIS - Pascal Luqman Setyaki; Muhammad Aji Nugroho; muhammad Gilang Fahmi Mubarok; Muhammad Iksanudin; Muhammad Ridwan Kusuma; Nur Yogisworo; Valiant Lukad Perdana Sutrisno; Petrus Sigit Nugroho (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2024)
This study investigates the effectiveness of active student learning strategies in improving both conceptual comprehension and practical application. The research explores how engaging students in active learning methods positively influences their understanding of concepts and enhances their ability to apply theoretical knowledge in practical settings. The study employs various instructional strategies designed to promote active participation and critical thinking among students, aiming to identify the most effective approaches for optimizing learning outcomes. The findings contribute valuable insights to educational practices by highlighting the significance of incorporating active learning strategies for a comprehensive and practical understanding of academic concepts.